HUBUNGAN ANTARA CORONAVIRUS CLINICAL CHARACTERIZATION CONSORTIUM (4C) DENGAN MORTALITAS PADA PASIEN CORONAVIRUS DISEASE (COVID-19) DI RUANG E RS BETHESDA YOGYAKARTA TAHUN 2022 - I.Wayan Sarba (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
ABSTRACT Background: The high incidence of Covid-19 has an impact on increasing the death rate. The high mortality rate of Covid-19 cases requires measuring tools in conducting assessments to predict the mortality rate of patients when they come to the hospital. A measuring tool that can be used to determine the prediction of the incidence of death by using the 4C. The data used in the 4C assessment included age, gender, comorbidities, respiratory rate, oxygen saturation, Glasglow coma scale (GCS), blood urea nitrogen, C- reactive protein (CRP).Objective: To determine the relationship of 4C and Mortality in Coronavirus Disease. Methods: The research is quantitative with design uses a retrospective correlation analysis approach. The sample was 78 people taken using proportional simple random sampling. The data collection method used questionnaires. Instrument with a mortality score of 4C. Data analysis of the two variables using the Somers test. Result: The results show is significant relationship between 4C and mortality in Covid-19 (p value <alpha = 0,000 <0.05) with a correlation of 0.756, namely high closeness. Conclusion: There is a relationship of Coronavirus Clinical Characterization Consortium and Mortality in Covid-19 Patients in Room E of Bethesda Hospital Yogyakarta in 2022. Suggestion: Further research is suggested to develop a 4C mortality score to predict the incidence of death in patients with other respiratory disorders.Keyword: Coronavirus Clinical Characterization Consortium , Mortalitas, Covid-19